Does firm's philanthropy lead to more missions: theory and evidence. Issue 1 (2nd September 2021) - He, Ling-Yun; Zhang, Hongzhen
Abstract : Purpose: Inspired by the comparison of charity donations among candidates in rural elections, the authors linked the non-profit motives of charity to corporate pollution emissions. And on this basis, the authors aim to provide theoretical and empirical explanations for the relationship between corporate philanthropy and pollution. The authors find that the desire to pursue more pollution emissions stimulates the firm's philanthropy, which is similar to the public welfare donations in rural elections. Design/methodology/approach: Firstly, the authors construct a game-theoretical framework consisting of an entrepreneur and a bureaucrat to study the environmental cost of corporate philanthropy through the impact on pollution emission by the firm. Secondly, the authors used various empirical methods, including hybrid OLS, IV-2SLS, PSM, etc., to empirically test the impact of a firm's philanthropy on corporate pollution emissions. Finally, the authors use the output and abatement input as intermediary variables and apply the intermediary effect model to test the impact mechanism between corporate philanthropy and corporate pollution emissions. Findings: Theoretical model finds that the firm invests more in philanthropy discharges more emissions when the theoretical model is in political equilibrium. Besides, empirical results show that corporate philanthropy will lead to more pollution emissions by reducing abatement input and increasing production. Finally, the heterogeneity test finds that compared with state-owned enterprises, the intention of non-state-owned enterprises' philanthropy for more pollution emission is more obvious. Moreover, the improvement of regional environmental regulation can significantly inhibit the realization of corporate philanthropy's poor motive. Practical implications: The results have obvious policy implications for China's future policy-making. Firstly, regulatory agencies should pay close attention to the charitable behaviors of firms with serious negative environmental externalities, and prevent them from replacing more pollution emissions with philanthropy. Besides, due to weak environmental supervision in rural areas, rural polluting enterprises will be more inclined to make charitable donations to the village collective to obtain more emission rights. Therefore, the government should strengthen environmental supervision in rural areas to prevent enterprises from wanton pollution. Originality/value: By constructing a game-theoretical framework consisting of an entrepreneur and a bureaucrat, the authors expound on corporate philanthropy's pollution motivation and decision-making mechanism for the first time in theory. Besides, this paper finds that the desire to pursue more pollution emissions also stimulates the firm's philanthropy. This paper expands the literature on corporate charitable donation motivations.